DEVELOPMENT OF STRATEGIC PLANNING ELEMENTS IN HEALTHCARE - Бабенко, Анатолий Иванович; Бабенко, Евгений Анатольевич (Medicine in Kuzbass, 2021)
Objective of research was to conduct a dynamic analysis of the scientific cognition regarding the development process of elements in the strategic planning for healthcare. Methods of research. The results of scientific research of the laboratory of medical and social problems and strategic planning in healthcare at Research Institute for Complex Problems of Hygiene and Occupational Diseases over the period of 1985-2021 were used. A content analysis of 600 scientific publications was carried out. Main results. The methodology and the main stages of strategic planning in healthcare were formed with the development of informational and analytical models of socio-hygienic assessment of the regional healthcare functioning, medical services and organizations. The characteristics of the main elements of strategic planning were given. The hierarchy of the health strategy, the levels of knowledge of problems was presented. The concept of health fund, its turnover and strategic significance of the population health indicators was defined. The list of the main scientific platforms for practical application of the developed elements and models was presented. Field of application. Regional and municipal healthcare, medical services and organizations. Conclusion. The presented theoretical and methodological developments of the laboratory, the stages, methods and models of strategic planning regarding territorial healthcare, medical services and organizations were the basis for the implementation of elements for strategic planning in healthcare.